Seychelles : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This paper reviews economic developments in Seychelles during 1990-95. After growing in 1992 and 1993 by 6.9 percent and 5.1 percent, respectively, real GDP contracted in 1994 by an estimated 1.6 percent, mainly as a result of a sharp decline in tourist receipts and a poor performance in the fishing sector. The annual rate of inflation as measured by the retail price index remained subdued at about 1.6 percent during 1993-94, compared with about 2.6 percent during the preceding two years.